High Stakes Testing in the 21st Century: Implications for Students in Special Education - Gordon, Lola (Journal of the American Academy of Special Education Professionals, 2016)
High-stakes testing has been a part of American education since its inception. The laws that govern the use of high-stakes tests include language that mandates the inclusion of students in special education. These laws play an influential role in the new large-scale assessments aligned with the Common Core State Standards (CCSS). The assessments being implemented in the current 2014-2015 school year include embedded and locally provided accommodations for students with a documented need. For students with the most severe cognitive disabilities alternate assessments are available aligned with the CCSS. The implications of these assessments and the role they play in crucial factors pertaining to students in special education requires additional research. Specific areas for research should include how high-stakes tests can be useful in identifying specific needs, accommodations, and strategies for learning for students in special education, and the role test scores play in retention and dropout rates for this population.